Subcellular Hsp70 Inhibitors Promote Cancer Cell Death via Different Mechanisms. Issue 10 (18th October 2018) - Park, Sang-Hyun; Baek, Kyung-Hwa; Shin, Insu; Shin, Injae
Summary: Mechanisms underlying cancer cell death caused by inhibitors of subcellular Hsp70 proteins have been elucidated. An inhibitor of Hsp70, apoptozole (Az), is mainly translocated into lysosomes of cancer cells where it induces lysosomal membrane permeabilization, thereby promoting lysosome-mediated apoptosis. Additionally, Az impairs autophagy in cancer cells owing to its ability to disrupt the lysosomal function. However, the Az-triphenylphosphonium conjugate, Az-TPP-O3, localizes mainly to mitochondria of cancer cells where it inhibits the mortalin-p53 interaction and induces mitochondrial outer membrane permeabilization, consequently leading to mitochondria-mediated apoptosis. Unlike Az, Az-TPP-O3 does not have an effect on autophagy in cancer cells. Collectively, the findings indicate that inhibitors of lysosomal Hsp70 and mitochondrial mortalin enhance cancer cell death via distinctively different mechanisms. Additionally, the findings arising from this effort demonstrate that studies aimed at determining subcellular locations and functions of small-molecule modulators provide a deeper understanding of their modes of action in cells. Graphical Abstract: Highlights: Inhibitors of different Hsp70 promote cancer cell death via different pathways An inhibitor of lysosomal Hsp70 induces LMP and promotes apoptosis An inhibitor of lysosomal Hsp70 impairs the autophagy process An inhibitor of mitochondrial mortalin induces MOMP and promotes apoptosis Abstract : Detailed mechanisms by which inhibitors of lysosomal Hsp70 and mitochondrial mortalin promote cancer cell death are unknown. Park et al. show that while an inhibitor of lysosomal Hsp70 induces apoptosis and inhibits autophagy, an inhibitor of mitochondrial Hsp70 induces apoptosis without affecting autophagy.